Novel biomarkers for cardiovascular risk. (21st August 2018) - Serra, Raffaele; Ielapi, Nicola; Barbetta, Andrea; Andreucci, Michele; de Franciscis, Stefano
Cardiovascular disease refers to different diseases involving the heart and/or the arteries and/or the veins. Cardiovascular disease, overall considered, is a notable source of morbidity and mortality worldwide. Therefore, several research studies are dedicated to explore, by means of biomarkers, the possiblity to calculate the cardiovascular risk both for the onset and for the complications of the related clinical manifestations such as coronary artery disease, carotid artery stenosis, peripheral artery disease, arterial aneurysm, chronic venous disease and venous thromboembolism. This review discusses the most updated information in the area of the novel biomarkers related to omics, imaging techniques and clinical data, that may help physicians in order to improve the knowledge and the management of the cardiovascular risk. Graphical abstract: Main biomarker families related to disease state in cardiovascular disease studied in the last 15 years. AA: Arterial aneurysm; CAD: Coronary artery disease; CAS: Carotid artery stenting; CVeD: Chronic venous disease; PAD: Peripheral artery disease; VTE: Venous thromboembolism.